El comportamiento de los estudiantes con deficiencia auditiva, de séptimo grado del Instituto Nacional de Audición y Lenguaje de la ciudad de Quito y su incidencia en el desarrollo afectivo. Período lectivo 2012-2013 - Rivadineira Romero, Patricia Belen (2013)
The following research work has been called: THE BEHAVIOR OF HEARING IMPAIRED STUDENTS, OF SEVENTH GRADE FROM THE NATIONAL INSTITUTE OF HEARING AND LANGUAGE OF QUITO AND ITS IMPACT ON THE EMOTIONAL DEVELOPMENT. LECTIVO PERIOD 2012-2013 and has been framed in the stipulated by regulations in force in the institution. The overall objective is: To illustrate the Educational Authorities Officers the importance of the behavior of the Students for Emotional Development, eliminating barriers to the integration of people with hearing impairments in educational processes. The methods used were: Scientist, Analytical-Synthetic; Inductive-Deductive, Descriptive, and Statistical Model. Techniques that were used are a Survey applied to the Seventh Grade Teachers of the National Institute of Hearing and Speech INAL from Quito City, in order to determine the behavior of Hearing Impaired Children, and a Questionnaire (Adapted from Woodworth test), to determine the incidence of Affective Development. According to the results of the Applied Survey to teachers to determine the behavior of Hearing Impaired Children, 100% indicates that the deaf child's behavior and /or Hearing Impaired are good. Likewise, 100% say Yes, Methodological Strategies seeking to integrate the Hearing Impaired students Teaching-Learning Process. Through the questionnaire for the Degree of Affection, Seventh Grade students of the National Institute of Hearing and Speech, of the city of Quito, reached a score of 7.5, which places them within the parameter of Affective Normal.